Konseling Online: Pemanfaatan Teknologi dalam Layanan Konseling Kelompok di SMP Global Islamic School Jakarta - Diana Syamila; Herdi Herdi (Jurnal Paedagogy, 2021)
This study aims to conduct online group counseling of students who are members of friendship groups with a qualitative experimental model that emphasizes the meaning of an event. This research method is descriptive by interpreting a collection of other articles as a study of literacy and the experience of reflection of the researchers during their practice in the field, which is then analyzed descriptively. The results of this study are the implementation of online group counseling by presenting seven group members and the homeroom teacher running effectively and producing positive results. Although only through the Zoom application with all its advantages and disadvantages, group counseling achieves the expected goals.